Subject: preventve vaccinatons in the prophylaxis of infectous diseases in children of clinical risk group - Kowacka, Ewa Beata (Journal of Education, Health and Sport, 2019)
Despite the past years and intensifying attacks of so-called anti-vaccinationists against the idea and practice of preventive vaccinations, especially in children, the opinion that they are “one of the greatest benefits and health achievements of humanity” remains valid1. The vaccine is a biological immune care product containing specific antigen or antigens that provide immunity to infection with one or more pathogenic microorganisms. The importance of implementing the concept of preventive vaccinations on the general scale consists primarily in the fact that they have eliminated from the life of societies, or at least from significant areas of the world known to us, traumatic experiences of epidemics decimating human communities, both on a local and regional, and sometimes even, as infamous Spanish influenza, which a hundred years ago consumed, as estimated even 100 million victims, on a global scale. As specialists point out, “even the invention of antibiotics has not had such a significant impact on reducing mortality and increasing human health. Vaccinations have significantly reduced the incidence of infectious diseases [...]. They practically eliminated diseases such as smallpox, diphtheria, tetanus, measles or poliomyelitis. Therefore, there is no doubt that the impact of vaccination on the health and development of each of us, regardless of age and gender, is unquestionable”2. In many modern countries, including Poland, the issue of preventive vaccinations, especially in children, is an inherent component of the state health policy. The scope, principles and procedures for the implementation of the Preventive Vaccination Schedule are regulated in the generally applicable provisions of law. However, it should not be forgotten that the introduction of any biologically active substance into the human body is not indifferent to its functioning. This consideration also applies to vaccines, and the risks associated with their administration are emphasized in particular in connection with preventive vaccinations in children. In view of the generally recognized achievements of medicine of infectious diseases and vaccinology, current vaccines are completely safe. The data of the World Health Organization (WHO) demonstrate that the probability of death because of their administration, as well as of the disease that they are supposed to protect against, is statistically so small that it is not really possible1. It does not change the fact that in certain cases preventive vaccinations should be preceded by a medical qualification test, and where appropriate, an assessment of the risk associated with the administration of the vaccine2. Therefore, before proceeding with the implementation of the POS, not only the legal aspect of this issue, but also clinical contraindications to the administration of the vaccine should be considered. Particular care and compliance with the legal procedures is recommended for the implementation of PSO in children and adolescents. This applies in particular to people of the group of clinical risk. It includes premature infants, children with immunodeficiency, cancer, rheumatic disease, after spleen removal, suffering from sickle cell disease, with allergy, cystic fibrosis, nervous system diseases, autoimmune diseases (e.g. diabetes), etc.3 Presentation of this issue in the context of legal conditions of preventive vaccinations in children and adolescents, as well as published research, is the primary purpose of this study.